Infrastructure development and economic complexity in South Africa Running title: Can infrastructure development influence economic complexity? - Chauke, Richard; Ncanywa, Thobeka (Technium Social Sciences Journal, 2021)
South African economy comprises of a narrow range of exports and an over-dependence on the primary production. These challenges hindered the growth and development of the country as well as the continent. One of the ways to enhance growth and development is through the improvement of economic complexity which measures productive capabilities of sophisticated products that countries export. The study seeks to find the role of investing in infrastructure development has on economic complexity using South African data. The autoregressive distributive lag approach was employed using yearly data spanning from 1960 to 2018. Results indicate that investing in government economic infrastructure has a negative and robust impact on economic complexity. Investment on government social infrastructure and public corporations’ infrastructure can positively influence economic complexity. It can be recommended that there should be policies to support industrial development that targeted incentivising economic infrastructure development. The development should prioritize specific geographical areas such as special economic zones to improve the lives of citizens, boost the economy, attract foreign direct investment and create jobs.